Ankle arthrodesis using a retrograde intramedullary rod with fins for highly destructive joints in elderly patients with rheumatoid arthritis: A report of two cases. Issue 2 (7th February 2022) - Takahashi, Shun; Kondo, Naoki; Kijima, Yasufumi; Kakutani, Rika; Ishikawa, Hajime; Kawashima, Hiroyuki
Abstract: Herein, we present two cases of older adult patients with highly destructive changes in ankle joints (Larsen grade IV) who underwent retrograde intramedullary ankle nail fixation with fins. In both patients, bony union was achieved, and full weight‐bearing was attained at 3 months after surgery. Abstract : Intramedullary retrograde ankle nails with fins improved postoperative functional outcome and disease activity score 28 in 2 cases with rheumatoid arthritis (RA) who had destructive ankle joints. These cases indicated that this implant is one of good options for elderly RA patients who affected destructive ankle joints.